Spaceborne tropospheric nitrogen dioxide (NO2) observations from 2005–2020 over the Yangtze River Delta (YRD), China: variabilities, implications, and drivers - H. Yin; H. Yin; Y. Sun; J. Notholt; M. Palm; C. Liu; C. Liu; C. Liu; C. Liu (Atmospheric Chemistry and Physics, 2022)
Nitrogen dioxide (NO2) is mainly affected by local emission and meteorology rather than long-range transport. Accurate knowledge of its long-term variabilities and drivers is significant for understanding the evolution of economic and social development, anthropogenic emission, and the effectiveness of pollution control measures on a regional scale. In this study, we quantity the long-term variabilities and the underlying drivers of NO2 from 2005–2020 over the Yangtze River Delta (YRD), one of the most densely populated and highly industrialized city clusters in China, using OMI spaceborne observations and the multiple linear regression (MLR) model. We have compared the spaceborne tropospheric results to surface in situ data, yielding correlation coefficients of 0.8 to 0.9 over all megacities within the YRD. As a result, the tropospheric NO2 column measurements can be taken as representative of near-surface conditions, and we thus only use ground-level meteorological data for MLR. The inter-annual variabilities of tropospheric NO2 vertical column density (NO2 VCDtrop) from 2005–2020 over the YRD can be divided into two stages. The first stage was from 2005–2011, which showed overall increasing trends with a wide range of (1.91 ± 1.50) to (6.70 ± 0.10) × 1014 molec. cm−2 yr−1 (p<0.01) over the YRD. The second stage was from 2011–2020, which showed overall decreasing trends of (−6.31 ± 0.71) to (−11.01 ± 0.90) × 1014 molec. cm−2 yr−1 (p<0.01) over each of the megacities. The seasonal cycles of NO2 VCDtrop over the YRD are mainly driven by meteorology (81.01 %–83.91 %), except during winter when anthropogenic emission contributions are pronounced (16.09 %–18.99 %). The inter-annual variabilities of NO2 VCDtrop are mainly driven by anthropogenic emission (69.18 %–81.34 %), except for a few years such as 2018 which are partly attributed to meteorology anomalies (39.07 %–91.51 %). The increasing trends in NO2 VCDtrop from 2005–2011 over the YRD are mainly attributed to high energy consumption associated with rapid economic growth, which causes significant increases in anthropogenic NO2 emission. The decreasing trends in NO2 VCDtrop from 2011–2020 over the YRD are mainly attributed to the stringent clean air measures which either adjust high-energy industrial structure toward low-energy industrial structure or directly reduce pollutant emissions from different industrial sectors.